Purification of Sharia Banking Law in the National Banking System - Ulya Atsani (Institut Agama Islam Negeri Batusangkar, 2022)
The development of sharia banking law can be seen from the accommodation of the state towards Islamic law in the field of sharia economics, including the development of sharia banking regulations. It is also due to the fact that the development of sharia banking regulations in Indonesia is based on the needs of the Indonesians whose majority are Muslims. During its development, sharia banking regulations have been carried through three stages, namely introduction, recognition, and purification. Meanwhile, the current legal fact shows that sharia banking existence does not meet its target of development, both institutionally and legally. To answer this problem, a normative legal method was used in conducting this research. The secondary data were qualitatively analysed concerning the purification of sharia banking law in the national banking system. The results shows that purifying sharia banking law can be done by strengthening the existence of sharia banking institutions through banking law policies. Refining the aspect of institutional can also be carried out by setting provisions regarding the settlement of sharia banking disputes in Indonesia.